Fat-cartilage axis: the regulation of IL-6/Osteopontin signaling in osteoarthritis of mice - Bing-yang Dai; Zhong-lian Huang; Ming-gui Bao; Hong-jiang Chen; Xiao-hui Lu; Jun Hu (Cell Death Discovery)
Abstract The infrapatellar fat pad (IPFP) acts as a bioactive reservoir, secreting proinflammatory cytokines that orchestrate both local and systemic inflammatory cascades. Despite its emerging role in knee osteoarthritis (OA) pathophysiology, the molecular and cellular mechanisms driving IPFP-mediated disease progression remain a critical gap in mechanistic understanding. 12-week-old male C57BL/6 mice underwent either destabilization of the medial meniscus (DMM) surgery or Sham surgery. Here, we find that the extreme sensitivity of IPFP makes it prone to act as a reservoir of inflammatory factors, which may indiscriminately disrupt the stability of its surrounding tissues. We further ascertain the role of IL-6 in initializing fibrosis in IPFP at early stage of OA and modulating osteopontin (OPN) secretion that cascades cartilage deterioration. Notably, removal of the IPFP in DMM mice reverses the abnormal functions of the knee joint. Compromising the progress of fibrosis by intra-IPFP injection of siRNA Cd61 or inhibition of OPN expression can drastically ameliorate cartilage deterioration. Our findings elucidate a pivotal role for IL-6 in instigating fibrotic remodeling within the IPFP during early-stage OA, concurrently regulating OPN secretion to propagate cartilage matrix degradation. This study thus establishes a conceptual framework for therapeutic intervention by targeting the IL-6/OPN signaling axis in the IPFP during OA initiation, offering a promising strategy to disrupt disease progression.